Foreign Direct Investments and Individual Income in Central Africa - Ngouhouo, Ibrahim; el-Mawazini, Khaled (Mediterranean Journal of Social Sciences, 2012)
This article employs a panel of double ordinary least squares to verify the sensitivity of income per capita to the influxof foreign direct investment (FDI) in the Economic and Monetary Community of Central Africa (EMCCA). Equally, it uses thegranger causality test based on the auto-regressive model, most especially the one recently developed by Toda and Yamamoto(1995) to establish the causality links between FDI and per capita income in the Economic and Monetary Community of CentralAfrica. Results obtained show that there exist a direct effect between FDI and income per capita in the entirety of EMCCA. Thegranger causality test shows contrarily that there is no link between FDI and income per capita in the EMCCA countries whereasthe Toda-Yamamoto finds a symmetric link among these variables in Equatorial Guinea, a unidirectional link of FDI towardsincome per capita in Congo, Gabon and Chad; and no link between the variables in the Republic of Central Africa andCameroon.